Isolation Of Genomic Dna And Construction Of Metagenomic Library From Marine Soil Sediments - R.PRABAVATHI; V.MATHIVANAN (International Journal of Pharma and Bio Sciences, 2012)
Microorganisms constitute two third of the earth’s biological diversity. As many as 99% of the microorganisms present in certain environments cannot be cultured by standard techniques. Culture-independent methods are required to understand the genetic diversity of microbial population, structure and ecological role of the majority of organisms. Metagenomics is the genomic analysis of microorganisms by direct extraction and cloning of DNA from their natural environment. To develop methods to investigate the full extent of microbial diversity, we have used a direct lysis method for the isolation of genomic DNA from soil sediments and also pWEB –TNC cosmid cloning kit have been used as a vector for construction of environmental metagenomic library for the detection of novel biocatalyst. To date, we have constructed a library , which contain 10,000 clones, further it will be submitted for functional based screening to detect the novel biocatalyst for various purpose.